2019
DOI: 10.1016/j.athoracsur.2019.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Management, and Outcomes of Intraoperative Catastrophes During Robotic Pulmonary Resection

Abstract: have also helped to promote the popularization of robotic VATS internationally. [5][6][7] Despite these encouraging trends for robotic thoracic surgery, there is a paucity of robust clinical data on intraoperative catastrophes, partly due to their relative

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 26 publications
2
39
0
1
Order By: Relevance
“…As the branching pattern of pulmonary vessels is diverse, dissecting around the arterial trunk of in LUL are intertwined to bronchi and veins, lead to a potential risk of uncontrollable intraoperative bleeding. As the left upper lobe lobectomy has been considered as the most challenging procedure technically, previous reports on conventional VATS have reported ndings with catastrophic rates of 1% to 1.5% and pulmonary arterial bleeding was more frequent during VATS left upper lobectomy [15][16][17] . It is necessary to clarify the relationship between the various branching patterns of pulmonary vessels and bronchi.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the branching pattern of pulmonary vessels is diverse, dissecting around the arterial trunk of in LUL are intertwined to bronchi and veins, lead to a potential risk of uncontrollable intraoperative bleeding. As the left upper lobe lobectomy has been considered as the most challenging procedure technically, previous reports on conventional VATS have reported ndings with catastrophic rates of 1% to 1.5% and pulmonary arterial bleeding was more frequent during VATS left upper lobectomy [15][16][17] . It is necessary to clarify the relationship between the various branching patterns of pulmonary vessels and bronchi.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, no clear relations among the various branching patterns of pulmonary vessels and bronchi are reported. As previous studies reported an intraopetaive vessels injury was more frequent during the left upper lobectomy [15][16][17] , this study anatomically analyzed the branches and courses of subsegmental PVs, which are characterized by considerable diversity in the branching patterns of blood vessels and bronchi, in the left upper lobe (LUL) of lung.…”
Section: Introductionmentioning
confidence: 99%
“…Novellis et al [2] reported an overall conversion rate of 6.2% (21/338) for major robotic lung resections, of which 1.1% (4/338) were due to bleeding. Other authors have reported overall conversion rates of 1.5%-9% with pulmonary artery or pulmonary vein injury resulting in conversion in 0.5%-2.6% [3][4][5][6][7] . In a retrospective multi-institutional study of 1,810 patients who underwent robotic anatomic pulmonary resections, Cao et al [4] reported intraoperative catastrophic events in 1.9% of patients Catastrophic events were associated with higher proportion of patients who underwent preoperative radiotherapy, higher perioperative mortality, longer operative times, and higher estimated blood loss.…”
Section: Introductionmentioning
confidence: 99%
“…The most common intraoperative bleeding complication during robotic lung resection is from an injury to the pulmonary artery. Most commonly, pulmonary artery injury occurs during dissection of the artery [4] . These injuries are easier to see as they occur directly at the point of dissection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation